Pengaruh Kepemimpinan, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Guru di SMK Penda 2 Karanganyar - Wicahyani, Evik; Handayani, Asih (Teewan Journal Solutions, 2025)
Human Resources (HR) is one of the causes of a company's success in achieving its goals. The human resources available in this case are teachers at SMK Penda 2 Karanganyar who are required to be able to provide maximum assessment to students in order to grow student potential. For this reason, one of the things a teacher must have is the ability to create teaching methods that can be understood by students. This research aims to analyze the significance of the influence of leadership, work discipline and work environment on teacher performance at SMK Penda 2 Karanganyar. The research method used is a quantitative method. The data source used in this research is primary data. The population in this study were all teachers at SMK Penda 2 Karanganyar. The sample used in this research was all 51 teachers at SMK Penda 2 Karanganyar. The sampling technique uses a non-probability sampling technique. The data collection techniques used were questionnaires, observation, interviews and literature study. Data analysis techniques use multiple linear regression tests, t tests, F tests, and coefficient of determination tests (R2 ). The results of the study, leadership, work discipline and work environment have a significant effect on the performance of teachers at SMK Penda 2 Karanganyar